Crafting Your Personal Brand and Finding Fulfillment in Colorectal Surgery - Walker, Avery (Clinics in Colon and Rectal Surgery, 2025)
As newly minted colorectal surgeons, you are skilled, driven, and compassionate. But what makes you you in this field? Your personal brand—your unique blend of personality, values, and approach to patient care—sets you apart and help you be successful clinically and professionally. Drawing from my own journey, this article explores how to build a personal brand and find fulfillment as a colorectal surgeon, tailored for those just starting out, but is relevant to those looking for the next step.
Keywords: colon and rectal surgery; brand; niche; authenticity; surgical development